Prevalence of idiopathic scoliosis in athletes: a systematic review and meta-analysis - Mousavi, L.; Seidi, F.; Minoonejad, H.; Nikouei, F. (BMJ Open Sport & Exercise Medicine, 2022)
Objective This study aimed to determine the prevalence of idiopathic scoliosis (IS) in child, adolescent and adult athletes of all sports activity levels.